Antonio Santa Croce and Giovanni Battista Pallotta – Cooperation between the Warsaw and Vienna Nunciatures in 1629. A Contribution to the Study of Horizontal Communication within the Structures of the Papal Diplomatic Service - Duda, Paweł; Litwin, Henryk (Legatio: The Journal for Renaissance and Early Modern Diplomatic Studies, 2023)
The article deals with communication and interaction between papal diplomatic missions in the early modern era. Mainly due to a lack of extant source materials, it remains the white spot in the research into the history of Polish and foreign nuncios. However, thanks to materials from Archivio di Stato di Roma, namely the section of Archivio Santa Croce containing the originals of letters received by Nuncio Antonio Santa Croce in 1629, it is possible to attempt at least a partial reconstruction of the collaboration between the papal diplomat residing at the Court of Warsaw and his counterpart at the Court of Emperor Ferdinand II of Habsburg in Vienna, Giovanni Battista Pallotta. The correspondence analysis allows us to conclude that the contacts between the papal diplomats residing in Warsaw and Vienna in 1629, and probably earlier and later, were regular and intensive. We can assume that the routine products of the information and analytical work carried out for the Secretariat of State by both papal missions were shared in the correspondence, and the Nunciatures of Vienna and Warsaw were thus well informed about the course of affairs related to the pan-European conflict in several theatres of war. However, they also communicated and cooperated on strictly ecclesiastical matters, such as the ongoing reform of religious congregations in the 1620s.